Worldwide Hospitality and Tourism Themes : How can the film-induced tourism phenomenon be sustainably managed? / Theme Editors: Noëlle O’Connor and Niki Macionis - Macionis, Niki Editors
Film-induced tourism is the collective term used for the study of tourist visits to a destination or attraction as a result of the destination being featured on the cinema screen, DVD, television or on video. The film-induced tourism phenomenon is a relatively new field of study, and so as yet, it is not fully understood nor explored, which means that this theme ebook is both timely and useful. In essence, this collection provides a unique and readable resource for anyone interested in this exciting aspect of the tourism industry